Analiza responsywności stron internetowych polskich bibliotek uniwersyteckich - Gmiterek, Grzegorz (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The paper presents the results of analysis on eighteen Polish university libraries websites. The subject of study was the website responsiveness regarding the level of their mobile-friendliness in terms of content alignment to mobile devices display capabilities.